Design and Simulation of Flexible Lower Limb Assisted Exoskeletons Based on the OpenSim - Feng Bolin; Song Peng; Li Ruiyuan; Wei Zuba; Li Qiang; Sun Xichang (Jixie chuandong)
Aiming at the problems of poor wearing comfort of current rigid exoskeletons, difficulty in matching exoskeleton joints with human body joints, and many restrictions on human body freedom, a flexible lower limb assisted exoskeleton is designed. The exoskeleton uses a flexible elastic belt energy storage device. When walking, it assists the muscles of the lower limbs of the human body. This study uses the OpenSim software to establish a simulation of man-machine interaction with the flexible exoskeleton. Aiming at realizing its optimal assisting scheme, a multi-joint assisting and single-joint assisting man-machine coupling model is established. The influence of different joint assisting combinations on human assisting and the influence of the man-machine coupling model of exoskeletons with different spring stiffness on knee joints, hip joints and ankle joints are studied. The results show that the single-joint assisting scheme is better than the multi-joint assisting scheme, and the assisting effect of the single-ankle joint assisting scheme is the best when the spring stiffness increases to 20 N/mm. The simulation results show that compared with the situation without wearing the ankle exoskeleton, the overall energy consumption of the human body and the stress on the main movement muscles of the calf during walking are reduced, and the burden on the wearer's muscles is reduced to achieve the purpose of assisting.